Nationally Recruited Telehealth Group-Based Cognitive Behavioral Therapy for Insomnia in Patients with Primary Brain Tumors: A Randomized NIH ORBIT Phase IIc Study - Ashlee R Loughan; Autumn Lanoye; Kelcie Willis; Amber Fox; Mary Bridgman; Nolan Wages; Youngdeok Kim; Alicia Zukas; Christopher Kleva (Neuro-Oncology Advances, 2026)
Abstract Background Sleep disturbance is common and undertreated in adults with primary brain tumors. Cognitive Behavioral Therapy for Insomnia (CBT-I) is the first-line, non-pharmacological treatment, yet its benefit in neuro-oncology has yet to be evaluated. This Phase IIc pilot assessed feasibility, acceptability, and meaningful effects of telehealth group-based CBT-I versus treatment as usual (TAU) in neuro-oncology. Methods Adults with primary brain tumors and chronic insomnia were randomized 1:1 to six weekly CBT-I sessions or TAU. Primary outcomes were feasibility of recruitment and longitudinal data collection, acceptability of CBT-I and study procedures, and changes in patient-reported insomnia severity, fatigue, and sleep quality. Results Recruitment met a priori feasibility benchmarks: Of the 84 patients screened, 96% were eligible, 86% consented, and 60 were randomized (CBT-I n=29; TAU n=31). Baseline data collection exceeded benchmarks, while longitudinal data collection was variable across outcomes. Patients deemed CBT-I as acceptable (86% intervention retention, 100% reporting improved sleep, 100% patient-recommendation), and provided high satisfaction ratings (>80%) across delivery, compensation, and most study procedures. On descriptive comparisons, CBT-I demonstrated greater preliminary acute improvements in insomnia severity (61% vs. 33%), fatigue (57% vs. 35%), and sleep quality (74% vs. 30%) than TAU, with medium-to-large effects (Cohen’s d = −0.69 to − 1.63 vs. d = −0.33 to − 0.73) observed on continuous measures. Conclusions Telehealth CBT-I is feasible, acceptable, and shows promising benefit signal in adults with primary brain tumors, particularly for improving insomnia. Future trials should optimize procedures for neurocognitive and accelerometer longitudinal data collection to support fully powered efficacy studies.